factor n 4 - 1

n^4 - 1 = (n2 + 1)(n + 1)(n - 1)

Question

Asked 6/25/2016 11:31:27 AM

Updated 6/25/2016 2:38:11 PM

1 Answer/Comment

Edited by jeifunk [6/25/2016 2:38:11 PM]

s

Rating

8

n^4 - 1 = (n2 + 1)(n + 1)(n - 1)

Added 6/25/2016 2:38:07 PM

This answer has been confirmed as correct and helpful.

-2x(x 2 - 3) **Weegy:** -2x(x^2 - 3) = - 2x^3 + 6x **User:** (2p + 7)(3p - 9)
**User:** 3y^2z(2y^2 z + 4yz - y + z) **Weegy:** 3y^2z(2y^2z + 4yz - y + z) = 3y^2z*2y^2z + 3y^2z*4yz - 3y^2z*y + 3y^2z*z = 6y^4z^2 + 12y^3z^2 - 3y^3z + 3y^2z^2 **User:** (6a + b)2 **Weegy:** (6a + b)^2 = 36a^2 + 12ab +b^2 **User:** (-d + 4)(-d - 4) **Weegy:** (-d + 4)(-d - 4) = d^2 + 4d - 4d - 16 = d^2 - 16 **User:** 5 + 2{x - 4[3x + 7(2 - x)]}.
**User:** (6z 2 - 4z + 1)(8 - 3z). **Weegy:** (6z^2 - 4z + 1)(8 - 3z) is equals to -18z^3 + 60z^2 - 35z + 8 **User:** (7q - 5)(7q + 5) **Weegy:** (7q - 5)(7q + 5) = 49q^2 - 25 **User:** -mnp(3m - 5n + 7p) **Weegy:** -mnp(3m - 5n + 7p) = -3m^2np + 5mn^2p - 7mnp^2 **User:** y 9 ÷ y 3 **User:** 48a^3 bc^2 ÷ 3abc **Weegy:** 48a^3 bc^2 / 3abc = 16a^2c **User:**
(35n 3 - 30n 2 + 25n) ÷ (-5n) **Weegy:** (35n^3 - 30n^2 + 25n) / (-5n) = -7n^2 + 6n - 5 **User:** (y 3 - 125) ÷ (y - 5)
**User:** Given: X = r + 2, Y = 2r - 9, and Z = r 2 + 17r + 30.
Simplify [X · Y - Z] ÷ X. **Weegy:** Given: X = r + 2, Y = 2r - 9, and Z = r^2 + 17r + 30. [X ? Y - Z] / X = [(r + 2)(2r - 9) - (r^2 + 17r + 30)]/(r + 2) = (2r^2 - 9r + 4r - 18 - r^2 - 17r - 30)/(r + 2) = (r^2 - 22r - 48)/(r + 2) = (r - 24)(r + 2)/(r + 2) = r - 24 (More)

Question

Updated 6/21/2016 4:19:51 AM

3 Answers/Comments

(2p + 7)(3p - 9)

= 2p*3p + 7*3p - 2p*9 - 7*9

= 6p^2 + 21p - 18p - 63

= 6p^2 + 3p - 63

= 2p*3p + 7*3p - 2p*9 - 7*9

= 6p^2 + 21p - 18p - 63

= 6p^2 + 3p - 63

Added 6/20/2016 10:12:43 PM

This answer has been confirmed as correct and helpful.

Confirmed by vchutkan [6/20/2016 10:16:46 PM]

5 + 2{x - 4[3x + 7(2 - x)]}

= 5 + 2{x - 4(3x + 14 - 7x)}

= 5 + 2{x - 4(-4x + 14)}

= 5 + 2{x + 16x - 56}

= 5 + 2{17x - 56}

= 5 + 34x - 112

= 34x - 107

= 5 + 2{x - 4(3x + 14 - 7x)}

= 5 + 2{x - 4(-4x + 14)}

= 5 + 2{x + 16x - 56}

= 5 + 2{17x - 56}

= 5 + 34x - 112

= 34x - 107

Added 6/20/2016 10:35:16 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/21/2016 4:19:31 AM]

factor m 4 - n 4 User: Factor z 3 + 2z 2 - 9z - 18 User: Factor a 3 - 3 + 3a 2 - a

Question

Updated 6/25/2016 2:37:03 PM

3 Answers/Comments

Factor x 2 + 13x + 36 **Weegy:** x^2 + 13x + 36 = (x + 9)(x + 4) **User:** factor a 2 - a - 20 **Weegy:** a^2 - a - 20 = a^2 - 5a + 4a - 5*4 = (a - 5)(a + 4) **User:** factor x 2 - 5x - 14 (More)

Question

Updated 6/25/2016 2:46:19 PM

1 Answer/Comment

x^2 - 5x - 14 = (x + 2)(x - 7)

Added 6/25/2016 2:46:19 PM

This answer has been confirmed as correct and helpful.

Factor 5x 4 - 30x 2 - 135 **Weegy:** 5x^4 - 30x^2 - 135 = 5 (x^2+3) (x-3) (x+3) **User:** Factor 2x 4 - 20x 2 - 78 **Weegy:** 2x^4 - 20x^2 - 78 = 2(x^4 - 10x^2 - 39) = 2(x^2 + 3)(x^2 - 13) (More)

Question

Updated 6/25/2016 2:39:37 PM

0 Answers/Comments

Factor 9y 2 - 12y + 4.

Question

Updated 6/25/2016 2:41:09 PM

1 Answer/Comment

z^2 + 18z + 81 = (z+9)(z+9) = (z+9)^2

Added 6/25/2016 2:41:09 PM

This answer has been confirmed as correct and helpful.

33,145,015

questions answered

There are no comments.